Labor supply and M&A in the audit market - Abramova, Inna (Journal of Accounting and Economics, 2024)
Using labor supply shocks from the 150-Hour Rule, I find that a reduction in the labor supply of accountants increases audit firms’ mergers and acquisitions (M&A) and the audit market concentration. These M&A deals connect audit firms serving clients in the same states and lead to greater industry specialization of the merging firms. Although both small and large auditors generally engage in labor supply–driven M&A deals, large audit firms’ engagement in M&A is restricted to markets with a tight supply of accounting labor. Attenuations of the labor supply restrictions tend to limit the heightened M&A activities and mitigate the rise in the audit-market concentration from the 150-Hour Rule. I conclude that labor supply reductions affect the boundaries of audit firms, potentially changing the structure of the entire audit market.